(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
Technological transformation has become a critical driver of performance improvement in healthcare organizations, particularly in public hospitals facing increasing service demands and operational challenges. Despite substantial investments in digital technologies, improvements in service quality are not always achieved, highlighting the importance of human factors in the digital transformation process. This study examines the impact of technological transformation on service quality in public hospitals, with a particular focus on the mediating role of employee digital competence. A quantitative research design was employed, and data were collected through a structured questionnaire distributed to employees working in public hospitals. A total of 165 valid responses were analyzed using SPSS and AMOS. Descriptive statistics, reliability analysis, correlation analysis, regression analysis, and exploratory factor analysis were conducted to test the proposed research hypotheses and validate the measurement model. The findings reveal that technological transformation has a significant positive effect on service quality and employee digital competence. In addition, employee digital competence was found to have a strong positive effect on service quality and to partially mediate the relationship between technological transformation and service quality. These results highlight the crucial role of digitally competent employees in maximizing the benefits of technological transformation in public hospitals.